1975
DOI: 10.1073/pnas.72.6.2380
|View full text |Cite
|
Sign up to set email alerts
|

A p60 polypeptide in the feline leukemia virus pseudotype of Moloney sarcoma virus with murine leukemia virus p30 antigenic determinants.

Abstract: A 60,000-dalton polypeptide (p60) has been identified in the feline leukemia virus (FeLV) pseudotype of Moloney sarcoma virus [MSV(FeLV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
20
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
(8 reference statements)
3
20
0
Order By: Relevance
“…The FeLV pseudotypes of ml and m3 Moloney murine sarcoma viruses have been described (5,6). The IC isolate of M-MuLV (5) was purified by double banding in sucrose gradients (2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The FeLV pseudotypes of ml and m3 Moloney murine sarcoma viruses have been described (5,6). The IC isolate of M-MuLV (5) was purified by double banding in sucrose gradients (2).…”
Section: Methodsmentioning
confidence: 99%
“…mlMSV P60, p30, p15, and p12 were purified from mlMSV(FeLV) (2,6); m3MSV P70 and p30, from m3MSV(FeLV) (5); and M-MuLV p30, from M-MuLV IC. Virus proteins were purified by guanidine agarose chromatography (6) or by polyacrylamide gel electrophoresis. For purification by the latter procedure, 1 mg of purified virus was subjected to a low-level dansylation procedure for visualization of the protein bands in the gel (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was very useful in the identification of mammalian sarcoma virus-specific nucleotide sequences, both those which were unique and those shared with the group from which the sarcoma virus was derived (Frankel et aL, 1976;Scolnick et al, 1975). Secondly, the identification of defective oncovirus precursor polyproteins was made 0022-1317/82/0000-5062 $02.00i~)1982 SGM Short communications easier in systems where the helper virus was genetically unrelated (Oskarsson et al, 1975;Robey et aL, 1977). We have previously studied the replication of MSV in a variety of mammalian cell lines with respect to both pP60 gag precursor formation and cleavage and found that MSV was genetically stable.…”
mentioning
confidence: 99%
“…In each of three cases most of the transformed cells stained as expected with anti-MuLV p30 serum because of the presence of the MSV p60 polyprotein, but 1 to 2% of cells also stained with anti-MuLV gp70 serum. Cells which were positive for MuLV gp70 had to be infected with an MuLV helper virus because this determinant is not encoded by the mlMSV (Oskarsson et al, 1975). On further passage of infected mink cells more MSV(B-MuX) virus became apparent.…”
mentioning
confidence: 99%